Mobile application for after school pickup solution Malaysia perspectives - Law, Check Yee; Sek, Yong Wee; Tay, Choo Chuan; Goh, Wei Wei (2023)
School pickup is a daily routine for most parents during the school term. The use of private vehicles as daily commute to transport students to and from schools has caused school-related traffic congestion and air pollution problems. The after school waiting bay of most schools in urban areas is normally very crowded with students waiting for transport to travel home. Teachers on duty and school student council members are assigned to monitor and control the crowded situation. Some schools implement drive-thru pickup procedure in which the teacher on duty need to be very attentive and observe the cars approaching the bay for pickup in order to queue up the students at the